ROLE AND RELEVANCE OF HUMAN RESOURCES MANAGEMENT IN CONTEMPORARY PROFIT-CENTRIC ERA - Momin, Mujtaba M. (Economic and Bussiness Faculty, Dr Soetomo University, 2018)
With ‘bottom-line’ and profits emerging as top priorities, the function of Human Resource Management is being expected to deliver value like never before. Contemporary Businesses and corporations are desperately exploring ways to cut costs and maximize value gained from every function. This Paper deals with the various challenges that the function of HRM is faced with in an increasingly profit-centric era. The major HRM challenges that distinctly stick out during financially challenging times are listed and briefly explained in this paper. In addition to that, the author has also suggested ways and means in which the function of HRM can add value and make a real business contribution.